2020
DOI: 10.1248/bpb.b19-00799
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Major Bleeding and Clinically Relevant Non-major Bleeding in Japanese Patients Treated with Edoxaban

Abstract: Edoxaban is used to prevent and treat stroke or systemic embolism such as venous thromboembolism. Although bleeding is the most common complication of anticoagulants, only a few studies have addressed the safety of direct oral anticoagulants in East Asian patients. In this study, we investigated the risk factors for bleeding in Japanese patients receiving edoxaban. A retrospective review of the records of 198 patients who received 30 mg/d edoxaban in our hospital between April 2015 and March 2017 was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Studies have shown that DOAC dose can be reduced in patients with the following clinical characteristics: elderly (≥ 75 years old), female, low weight (≤ 60kg), renal insu ciency (CrCl ≤ 50ml/min), previous bleeding history, combined history of hypertension, combined use of dronedarone or antiplatelet drugs, etc. [11] Studies have shown that Asian patients with low body weight, cancer, low baseline hemoglobin levels, prolonged prothrombin time, and low creatinine clearance are at increased risk of edoxaban related bleeding [12][13][14] . This study found that the clinical characteristics of patients taking low-dose DOAC regimen included: age ≥ 80 years old, weight ≤ 60kg, ADL score ≤ 60 points, HAS-BLED score ≥ 3.0 points, eGFR < 60ml/min/1.73m², and baseline hemoglobin < 120g/L.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DOAC dose can be reduced in patients with the following clinical characteristics: elderly (≥ 75 years old), female, low weight (≤ 60kg), renal insu ciency (CrCl ≤ 50ml/min), previous bleeding history, combined history of hypertension, combined use of dronedarone or antiplatelet drugs, etc. [11] Studies have shown that Asian patients with low body weight, cancer, low baseline hemoglobin levels, prolonged prothrombin time, and low creatinine clearance are at increased risk of edoxaban related bleeding [12][13][14] . This study found that the clinical characteristics of patients taking low-dose DOAC regimen included: age ≥ 80 years old, weight ≤ 60kg, ADL score ≤ 60 points, HAS-BLED score ≥ 3.0 points, eGFR < 60ml/min/1.73m², and baseline hemoglobin < 120g/L.…”
Section: Discussionmentioning
confidence: 99%
“…A lower baseline Hgb level was also a significant risk factor for bleeding in Japanese patients receiving Edx. [ 21 ] The implications of this association between the baseline Hgb levels and renal function for Edx treatment are interesting and should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of major or clinically relevant nonmajor bleeding events related to edoxaban was reported to range from 3.8 to 19.2% [ 15 – 19 ]. Studies indicated that the risk factors of DOAC-related bleeding events include heavy alcohol use, uncontrolled hypertension, increasing age, heart failure, vascular disease, antiplatelet use, chronic renal failure, and diabetes mellitus [ 17 , 20 ]. In our case, the patient’s age and comorbidities, including excess alcohol use, carotid artery stenosis, arteriosclerosis obliterans, and diabetes mellitus, possibly increased the risk of DOAC-related hematoma.…”
Section: Discussionmentioning
confidence: 99%